Peran Levers of Control Terhadap Hubungan Antara Perencanaan Strategis dan Kinerja UMKM - Praja Hadi Saputra; Hamid Bone; Indah Permatasari (Jurnal Inovasi Bisnis dan Kewirausahaan, 2019)
This study investigates the role of levers-of-control (LOC) based controlling system in the strategy formulation and MSME performance relationship in Samarinda. Through a survey conducted on the leadership (controller) of MSMEs in Samarinda City, this study evidenced the role of management control systems in the strategy formulation and MSME performance relationship. Of the 49 responses of MSME leaders, processed using PLS-SEM analysis, this study provided empirical evidence that the strategy formulation had a positive relationship with MSME performance. In addition, the indirect relationship between the two (mediation) through LOC-based management system supported the mediation hypothesis that the LOC-based management control system affects the strategy formulation and MSME performance relationship. In other words, it can be concluded that the management control system can increase the strategy formulation role that leads to MSME performance betterment.